Multilayered regulation of proteome stoichiometry - Ishikawa, Koji (Current genetics, 2021)
Cellular systems depend on multiprotein complexes whose functionalities require defined stoichiometries of subunit proteins. Proper stoichiometry is achieved by controlling the amount of protein synthesis and degradation even in the presence of genetic perturbations caused by changes in gene dosage. As a consequence of increased gene copy number, excess subunits unassembled into the complex are synthesized and rapidly degraded by the ubiquitin-proteasome system. This mechanism, called protein-level dosage compensation, is widely observed not only under such perturbed conditions but also in unperturbed physiological cells. Recent studies have shown that recognition of unassembled subunits and their selective degradation are intricately regulated. This review summarizes the nature, strategies, and increasing complexity of proteinlevel dosage compensation and discusses possible mechanisms for controlling proteome stoichiometry in multiple layers of biological processes.
Gesehen am 10.07.2023